2013
DOI: 10.4049/jimmunol.1203172
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Pathogenicity of IFN-γ–Producing Th17 Cells Is Independent of T-bet

Abstract: During the development of experimental autoimmune encephalomyelitis (EAE), the proportion of pathogenic and myelin-specific cells within CNS-infiltrating cytokine producing T helper (Th) cells is unknown. Using an IL-17A-IFN-γ double reporter mouse and I-Ab/MOG38–49 tetramer, we show here that IL-17+ IFN-γ+ Th cells, which are expanded in the CNS during EAE, are highly enriched in MOG-specific T cells. We further demonstrate that IL-23 is essential for the generation and expansion of IFN-γ producing Th17 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
148
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 23 publications
11
148
2
1
Order By: Relevance
“…Interestingly, however, in each of these studies, a population of IL-17A + IFN-γ + T cells developed in the absence of T-bet expression by CD4 + T cells, consistent with findings herein. Whereas these dual positive cells appear to be nonpathogenic in the intestines, their presence was associated with disease in EAE in at least one study (31). These findings expose likely differences between pathogenesis in the intestines and CNS.…”
Section: Wt Th17pmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, however, in each of these studies, a population of IL-17A + IFN-γ + T cells developed in the absence of T-bet expression by CD4 + T cells, consistent with findings herein. Whereas these dual positive cells appear to be nonpathogenic in the intestines, their presence was associated with disease in EAE in at least one study (31). These findings expose likely differences between pathogenesis in the intestines and CNS.…”
Section: Wt Th17pmentioning
confidence: 75%
“…Interestingly, other studies suggest that T-bet expression by T cells is not absolutely required for EAE pathogenesis, although disease was blunted in its absence (31,32). This finding might reflect differences in the role of T-bet in the Th17 to Th1 transition of Th17 cells differentiated ex vivo versus those that differentiate in vivo, which warrants further study.…”
Section: Wt Th17pmentioning
confidence: 93%
“…Stimulation of memory CD4 + T cells with IL-12p70 promotes memory CD4 + T cell proliferation and IFN-γ production (Oppmann et al, 2000). The role of IL-12p70 in promoting transition of memory Th17 cells towards Th1 phenotype was previously reported (Annunziato et al, 2007, Duhen et al, 2013. Duhen et al demonstrated that IL-12p70 in combination with IL-1β enhanced T-bet and STAT4 expression in memory Th17 cells, leading to production of IL-17A, IFN-γ and GM-CSF (Duhen et al, 2013).…”
Section: 51) Effects Of Il-12p70 and Il-23 On Memory Cd4 + T Cellsmentioning
confidence: 79%
“…induces IFN-γ IL-17A-double producing T cells and repression of IL-10 induction (Duhen et al, 2013, Ramesh et al, 2014 (Figure 1.2). Stimulation of memory CD4 + T cells with IL-12p70 promotes memory CD4 + T cell proliferation and IFN-γ production (Oppmann et al, 2000).…”
Section: 51) Effects Of Il-12p70 and Il-23 On Memory Cd4 + T Cellsmentioning
confidence: 97%
See 1 more Smart Citation